Scrolling into Crisis: Social Comparison as a Predictor of Quarter-Life Crisis among Emerging Adults on TikTok - Syafira Suniyah Nur Fahmi; Sarita Candra Merida; Sandra Adetya (Utan Kayu Publishing, 2026)
The rapid development of social media, particularly TikTok, has increased social comparison among emerging adults. Algorithm-driven content often presents curated portrayals of success, ideal lifestyles, and appearance, which may influence users’ self-evaluations. During emerging adulthood, a phase marked by identity exploration and instability, such exposure may contribute to psychological distress, including quarter-life crisis. This study aimed to examine social comparison as a predictor of quarter-life crisis among TikTok users. A quantitative correlational design was employed with 116 emerging adults in Bekasi City selected through purposive sampling. Data were collected using social comparison and quarter-life crisis scales with acceptable psychometric properties. Data were analyzed using simple linear regression. The results showed that social comparison significantly predicted quarter-life crisis (p < .001), with an R² value of 0.651, indicating that 65.1% of the variance in quarter-life crisis is explained by social comparison. These findings indicate that social comparison contributes substantially to vulnerability to quarter-life crisis. The study emphasizes the importance of media literacy and self-regulation to mitigate its negative psychological impact. Abstrak: Perkembangan pesat media sosial, khususnya TikTok, telah meningkatkan kecenderungan perbandingan sosial pada dewasa awal. Konten berbasis algoritma sering menampilkan gambaran yang telah dikurasi mengenai kesuksesan, gaya hidup ideal, dan penampilan, yang dapat memengaruhi evaluasi diri pengguna. Pada masa dewasa awal, yang ditandai dengan eksplorasi identitas dan ketidakstabilan, paparan tersebut dapat berkontribusi pada tekanan psikologis, termasuk quarter-life crisis. Penelitian ini bertujuan untuk menguji perbandingan sosial sebagai predictor quarter-life crisis pada pengguna TikTok. Pendekatan kuantitatif dengan desain korelasional digunakan pada 116 dewasa awal di Kota Bekasi yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan skala perbandingan sosial dan quarter-life crisis yang memiliki kualitas psikometrik yang memadai. Analisis data dilakukan dengan regresi linear sederhana. Hasil menunjukkan bahwa perbandingan sosial berpengaruh signifikan terhadap quarter-life crisis (p < 0,001), dengan nilai R² sebesar 0,651, yang berarti 65,1% variasi quarter-life crisis dijelaskan oleh perbandingan sosial. Temuan ini menegaskan pentingnya literasi media dan regulasi diri untuk mengurangi dampak psikologis negatif.